BLACK SOLDIER FLY (HERMETIA ILLUCENS) LARVAE OIL: A SYSTEMATIC LITERATURE REVIEW OF CHARACTERISTICS, APPLICATIONS, AND FUTURE RESEARCH DIRECTIONS - Magda Jeane Bera; Dwi Nowo Martono; Sri Wahyono (JURNAL ILMIAH EDUNOMIKA, 2026)
Black Soldier Fly (BSF) (Hermetia illucens) larvae oil has attracted increasing attention as a sustainable alternative lipid source due to its high fatty acid content, particularly lauric acid, and its potential applications across various sectors. This study aims to systematically review the current state of research on BSF larvae oil. A systematic literature review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant articles were retrieved from Scopus and ScienceDirect databases. Results showed that research on BSF larvae oil has grown substantially in recent years, with the majority of studies focusing on animal nutrition, aquaculture, growth performance, lipid metabolism, and feed efficiency. Bibliometric analysis revealed five major research clusters covering feed applications, fatty acid composition, growth performance, physiological responses, and alternative applications such as biodiesel. Overlay visualization showed a recent shift from basic feed utilization studies toward investigations of gut microbiota, lipid metabolism, and health-related effects. Research on industrial applications, cosmetic products, household cleaning products, and commercialization aspects remains limited.